The Role of Civic Education Teachers in Improving Students' Political Awareness in the Digital Era - Putri, Heliza Kamelia (International Journal of Students Education, 2025)
Citizenship education plays an important role in shaping character and increasing national and state awareness in Indonesia. The digital era has brought significant changes in the way people access information and participate in political life. This research aims to identify effective strategies used by civics teachers in increasing students' political awareness in the digital era. This research uses a literature review method to identify educational strategies that can be implemented to strengthen national awareness and foster a national spirit among the younger generation. This means education intended for to mature participant educate to be able to grow and develop in a way Correct so that can develop talents, potential and skills. Students is generation young people who play a role big in maintain leadership in the future. Through [research methods], this research found that Civics teachers use various approaches, such as project-based learning, group discussions, and the use of social media, to increase student engagement in Civics learning. Apart from that, teachers also act as models for students in showing critical and participatory attitudes in national and state life. The results of this research provide important implications for the development of the Civics curriculum and teacher training in facing the challenges of the digital era.